The Albumin-to-Fibrinogen Ratio Independently Predicts Acute Kidney Injury in Infants With Ventricular Septal Defect Undergoing Cardiac Surgery With Cardiopulmonary Bypass - Cao, Fan; Chen, Xinxin; Huang, Guodong; Liu, Wenhua; Zhou, Na; Yuan, Huili; Zou, Minghui (Frontiers in Pediatrics, 2021)
Background: Acute kidney injury (AKI) is a common and serious complication for children following ventricular septal defect (VSD) surgery with cardiopulmonary bypass (CPB). The objective of this study was to explore potential predictors for AKI. Methods: VSD infants who were scheduled for elective cardiac surgery with CPB from 2017 to 2020 were enrolled in this study. Based on the pRIFLE criteria, patients were divided into AKI and non-AKI groups. Univariate and multivariate logistic regression analyses were carried out to evaluate potential risk factors for AKI. Receiver operating characteristic (ROC) curves were generated to evaluate the predictive probabilities of risk factors for AKI. Results: Of all the 338 enrolled VSD infants, 49 occurred AKI with an incidence of 14.5% (49/338). The ROC curve indicated AFR during CPB was a significant predictor for AKI (AUC: 0.711, P < 0.001). Based on the univariate and multivariate logistic analyses, AFR during CPB (OR: 1.89, 95%CI: 1.22-2.76, P=0.011) was the only independent risk factor for AKI. Conclusions: This study demonstrated that a low AFR (< 9.35) during CPB was an independent risk factor for AKI in VSD infants after cardiac surgery with CPB.